Physico-Chemical And Sensory Characteristics Of Blends Of Palm Olein And Other Vegetable Oils And Their Frying Stability - Myat, Myat Win (2010)

(untitled)
Palm olein can easily be blended with other oils such as sesame and peanut oils. In this study, vegetable oil blends were prepared by blending, palm olein (PO) with sesame seed oil (SSO) or peanut oil (PnO) in proportions of 90:10, 80:20, 70:30 and 60:40 (v/v). The objectives of this study were to determine the physico-chemical characteristics of pure palm olein, sesame, peanut and their blends; to evaluate the sensory properties of banana chips fried in different oil blends in order to elucidate the best combination ratios to be used as frying oil; to determine the frying quality of palm olein blended with either PnO or SSO during deep fat frying; and to identify the best oil blends amongst them. In this study, the physico-chemical properties of oil blends such as fatty acid composition (FA), color, viscosity, free fatty acid (FFA), iodine value (IV), peroxide value (PV), p-Anisidine value (p-AV), total oxidation (TOTOX) value, triacylglycerol (TAG) profile and melting point were investigated.